Changes in the unilateral nasal resistance under stellate ganglion block - IKOMA, Hisaaki; TAKEUCHI, Hiromi; YAMAMOTO, Yuuko; HIGAMI, Yumiko; HIGAMI, Shigeru (OTOLOGIA FUKUOKA, 2000)
Stellate ganglion block (SGB) has been used in order to investigate the effect of autonomic nervous system on nasal patency. The nasal resistance (NR) on the side of SGB is recognized to be increased, whereas it is debatable whether NR on the contrarateral side is increased or decreased. The aim of this study is to investigate the relationship between the changes of unilateral NR in nasal cycle and under SGB. Nine healthy subjects (8 males and 1 female, aged 22-25 years) were recruited for the study. Unilateral NR was measured hourly over 7 hour period using the technique of anterior rhinomanometry. SGB was done with 1% lidocaine 5ml. Unilateral NR under SGB was measured at interval of 2 minutes over 60 minutes period. Unilateral NR on contralateral cavity under SGB was increased in 3 subjects, decreased in 5 subjects and unclassified in 1 subject. There was no relationship between the changes of unilateral NR in nasal cycle and under SGB. The results indicate that there would be multiple mechanisms in the change of unilateral NR under SGB.